2012
DOI: 10.1021/jp3032176
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Chemical and Magnetic Order in FeRh Clusters

Abstract: The structure, chemical order, and magnetic behavior in small FeRh clusters having N ≤ 19 atoms have been investigated theoretically. For N ≤ 6 atoms, a thorough global geometry optimization is performed by considering all possible cluster topologies, while for 7 ≤ N ≤ 19 only a few representative structures are considered. In all cases, the starting structures are fully relaxed in the entire range of concentrations and spin polarizations. The calculations are based on a generalized-gradient approximation to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 72 publications
4
8
0
1
Order By: Relevance
“…Our results are in line with an earlier study by Hamilton et al who reported similar stabilities of square-based pyramidal sp and trigonal bipyramidal tbp Rh 5 motifs in [Rh 5 (N 2 O)Ar] + clusters [41]. Other studies on various levels of theory on neutral and anionic rhodium clusters report similar results [26,43,[48][49][50][51]: low energy differences of nonet square pyramid 9 sp and trigonal bipyramid isomers tbp.…”
Section: Dft Modellingsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with an earlier study by Hamilton et al who reported similar stabilities of square-based pyramidal sp and trigonal bipyramidal tbp Rh 5 motifs in [Rh 5 (N 2 O)Ar] + clusters [41]. Other studies on various levels of theory on neutral and anionic rhodium clusters report similar results [26,43,[48][49][50][51]: low energy differences of nonet square pyramid 9 sp and trigonal bipyramid isomers tbp.…”
Section: Dft Modellingsupporting
confidence: 93%
“…DFT modelling of [Rh 5 (N 2 O)Ar] + cluster complexes revealed a low energy difference of square-based pyramidal (sp) and trigonal bipyramidal (tbp) Rh 5 motifs beyond a definite assignment [41]. Other studies at various levels of theory report similar results on neutral and anionic rhodium clusters [26,43,[48][49][50][51]: There are low energy differences of nonet square pyramid and trigonal bipyramid isomers.…”
Section: Introductionmentioning
confidence: 64%
“…This fact opens the possibility for a wide range of technological applications, such as magnetic storage [7][8][9][10], and heterogeneous catalysis [2,[11][12][13][14]. This possibility, along with the novel and interesting properties found on those systems, motivated a large number of experimental and theoretical studies [15][16][17] focusing on binary TM clusters, such as PtPd [18,19], PdIr [20], PtNi [21], PtRh [22], FeRh [10,23], and PtCu [24][25][26][27][28], with the aim to understand the behaviour of their physical and chemical properties as a function of the number of atoms, compositions, structure, and charge states.…”
Section: Introductionmentioning
confidence: 99%
“…77,78 The optimized geometries are in general compact with a strong tendency to intermixing in order to maximize the number of FeRh nearest-neighbour (NN) bonds. A very rich variety of structural and magnetic behaviour has been revealed.…”
Section: Ferh Corh and Copt Alloy Clustersmentioning
confidence: 99%